2011
DOI: 10.1530/eje-11-0545
|View full text |Cite
|
Sign up to set email alerts
|

Low 25(OH)D3 levels are associated with total adiposity, metabolic syndrome, and hypertension in Caucasian children and adolescents

Abstract: Objectives: Evidence of the association between vitamin D and cardiovascular risk factors in the young is limited. We therefore assessed the relationships between circulating 25-hydroxyvitamin D 3 (25(OH)D 3 ) and metabolic syndrome (MetS), its components, and early atherosclerotic changes in 452 (304 overweight/obese and 148 healthy, normal weight) Caucasian children. Methods: We determined serum 25(OH)D 3 concentrations in relation to MetS, its components (central obesity, hypertension, low high-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
124
5
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 73 publications
(69 reference statements)
21
124
5
7
Order By: Relevance
“…44 Similarly, a study in Caucasian children also found that central obesity, hypertension, hypertriglyceridemia, low HDL-C levels, and metabolic syndrome were associated with low 25(OH)D levels. 45 Despite the fact that in our study vitamin D was assessed only by nutritional intake, our results are in line with those of these investigations by showing that adolescents in the lowest vitamin D intake quartile group had an OR of 3.35 for high cardiometabolic risk score compared with the highest vitamin D intake quartile group after adjustment for several confounders. Nevertheless, the association between vitamin D intake and cardiometabolic risk is only significant for the lowest quartile.…”
Section: Discussionsupporting
confidence: 90%
“…44 Similarly, a study in Caucasian children also found that central obesity, hypertension, hypertriglyceridemia, low HDL-C levels, and metabolic syndrome were associated with low 25(OH)D levels. 45 Despite the fact that in our study vitamin D was assessed only by nutritional intake, our results are in line with those of these investigations by showing that adolescents in the lowest vitamin D intake quartile group had an OR of 3.35 for high cardiometabolic risk score compared with the highest vitamin D intake quartile group after adjustment for several confounders. Nevertheless, the association between vitamin D intake and cardiometabolic risk is only significant for the lowest quartile.…”
Section: Discussionsupporting
confidence: 90%
“…The potential effects of VitD on glucose homeostasis are considered to be mediated by autocrine and paracrine functions involving the transcriptional regulation of genes in pancreatic b-cells, skeletal myocytes and immune cells, improving insulin secretion and sensitivity and reducing inflammation (13,16) . Despite theoretical links between VitD and insulin sensitivity and/or secretion, controversy remains regarding the relationship between 25(OH)D levels and surrogate indices of insulin sensitivity (4)(5)(6)(7)25,26) or b-cell function (7,25,26) and the risk of glucose intolerance or T2DM (6,9,27) . These discrepancies in the relationships between VitD status and outcomes related to glucose homeostasis in paediatric or adult populations may be attributable to differences in study sample size, participant characteristics (race, ethnicity and degree of obesity), method of measuring insulin sensitivity and/or b-cell function, and the adjusted markers of adiposity used.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, low 25-hydroxyvitamin [25(OH)D] concentration have been found to be associated with higher risk of hyperglycemia, insulin resistance, and type 2 diabetes [5] . In children, limited vitamin D data show an association with fasting hyperglycemia and insulin resistance [6,7] . Animal data show impaired insulin secretion during vitamin D deficiency [8] and an improvement in insulin secretion with vitamin D supplementation [9,10] .…”
Section: Introductionmentioning
confidence: 99%